The role and function of the palliative care nurse practitioner in Israel. (2nd April 2019) - Haron, Yafa; Romem, Anat; Greenberger, Chaya
Abstract : Background: Research studies emphasise the importance of the nurse practitioner (NP) role in the continuum of care, patient health outcomes, and the formation of a positive work environment. There are different reports about the extent of care delivered by the nurse practitioner in different fields of expertise and in different countries. Aim: To present the characteristics of nurse practitioners in Israel, the extent of the role and practice, activities, role responsibilities, and job satisfaction. Methods: A descriptive computerised survey targeted palliative care nurse practitioners (PCNP). The study included nurses from all regions and districts in Israel, regardless of the nurses' health maintenance organisation or hospital affiliations. Results: NPs reported performing fewer frequent physical assessments, medication prescriptions issued, and lab and imaging referrals. Conclusion: The complexity of the implementation of the NP role requires prior planning for role introduction, mentorship for the NP, and understanding of the interface between the NP and other professional staff.